Anastasia Papathanasiou, William A. Parkinson, Daniel J. Pullen, Michael L. Galaty and Panagiotis Karkanas (eds). Neolithic Alepotrypa cave in the Mani, Greece. In honor of George Papathanassopoulos - Perlès, Catherine (Journal of Greek Archaeology, 2019)
Since the occupation of caves became recognised as a specific feature of the Late and Final Neolithic in Greece, widely differing interpretations have been offered. Schematically, the balance shifted from a purely pragmatic interpretation – caves were used as domestic places in the context of increasing pastoralism – to a mostly or purely ritual interpretation. However, as illustrated by a recent publication devoted to the use of caves, the question is far from settled. Yet, to better understand the status of LN/FN caves, or, more precisely, to better grasp how difficult it is to understand it, a key element was missing: the detailed publication of Alepotrypa Cave, in the Mani. More than any other cave site, Alepotrypa, with its apparently domestic occupations, wealth of human remains and exceptional deposits, epitomises the impossibility to draw a clear-cut opposition between the mundane and the ritual, the polis and the necropolis. Paradoxically, Alepotrypa raises not such much the question of the definition of rituals as the definition of what is domestic.